Determination of the Consumption of Spare Parts for Components and Systems of Vehicles During the Period of Operation - Toxirjon o‘g‘li, Karimov Islomjon; Jovliyev, Vasik Ulashevich; Inomjon-o‘g‘li, Otaqo‘ziyev Doniyor (European Journal of Life Safety and Stability (2660-9630), 2023)
In the period of market relations, the reliability of vehicles operating in transport processes and their costs are of particular importance. They depend not only on the quality of the cars, but also on their performance and handling. During operation, changes occur in the technical condition of the vehicle and its aggregates and systems, which leads to partial or complete loss of performance.